Primary schooling, human capital, and COVID-19: A multidimensional evaluation: Upcoming evidence from Mozambique - Chimbutane, Feliciano; Herrera-Almanza, Catalina; Karachiwalla, Naureen; Lauchande, Carlos; Leight, Jessica (International Food Policy Research Institute, 2021)
This evaluation encompasses two related investigations. The first is a randomized controlled trial evaluating the impacts of school meals and literacy programs that will launch when Mozambican primary schools reopen from COVID-19 closures; the evaluation will measure the effects of the interventions on early-grade student outcomes, including nutrition, reading, and school attainment. The second analyzes the effects of school closures due to COVID-19 on schooling attainment, well-being, and mental health among young adolescents in the same schools, particularly adolescent girls.